REPRESENTATION OF THE CONCEPT OF HOSPITALITY IN ENGLISH AND UZBEK PHRASEOLOGICAL UNITS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article explores the representation of the concept of hospitality in English and Uzbek phraseological units. Hospitality, as a culturally significant value, is deeply embedded in the linguistic worldview of both nations. The study aims to identify similarities and differences in the semantic, structural, and cultural aspects of phraseological expressions related to hospitality. The research employs comparative and linguocultural analysis methods. The findings reveal that while hospitality is universally valued, its linguistic realization reflects unique cultural priorities and social norms in each language.